Pembinaan dan Pengawasan Perbankan: Rekonstruksi Kewenangan Bank Indonesia dan Otoritas Jasa Keuangan dalam Sistem Hukum Keuangan Nasional - Difky Maulana; Restu Ramania; Yoga Ammar Arifin (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study comprehensively examines the legal aspects of separating the functions of banking supervision and development in Indonesia within the context of national financial institutional reform. The research focuses on the role of Bank Indonesia as the supervisory and developmental authority and the urgency of establishing an independent institution, namely the Financial Services Authority (OJK). The idea of separation emerged from the evaluation of Bank Indonesia’s performance in overseeing the banking sector following the 1998 economic crisis, where weak supervision contributed to financial instability. This research employs a juridical-sociological approach with a descriptive-analytical nature. The juridical approach analyzes legal norms contained in Law No. 23 of 1999 in conjunction with Law No. 3 of 2004 on Bank Indonesia and Law No. 10 of 1998 on Banking, while the sociological approach assesses their implementation effectiveness. The findings reveal that Bank Indonesia holds four key supervisory powers: licensing, regulation, control, and sanctioning. However, its dual role as a monetary authority and banking supervisor creates potential conflicts of interest and reduces supervision efficiency. Therefore, the separation of supervisory and developmental functions is a necessary institutional and legal reform to strengthen governance, enhance accountability, and ensure the stability of Indonesia’s financial system.